Pemaknaan Pelaku Usaha Dalam Pengembangan Pangan Lokal Di Kabupaten Lombok Barat - Eka Nur Jannah; Sri Peni Wastutiningsih; Partini Partini (Agro Ekonomi, 2016)
This study has the purpose to explain the meaning of business actors in the development of local food in West Lombok and explain the meaning of busines actors towards the involvement of primary and secondary stakeholders in the development of local food in West Lombok. This study used a qualitative method with phenomenological approach. Selection of a method purposive. Selection of informants using methods purposive ie businesses which process local food derived from terrestrial plant. The results showed that the meaning of efforts in the development of local food is positive as it can be an additional source of income for families, create jobs and expand social networks, but variations in the types of processed and flavor is still less diverse and less than optimal marketing. Primary and secondary stakeholders involved in the development of local food by providing assistance and motivation to constantly improve the quality and quantity of processed food products locally as well as marketing. But some stakeholders are not optimal involvement in the development of local food. The lack of optimization due to a lack of common ground between the businessmen and the stakeholders as well as between the stakeholders. Looking forward there are organizations that can coordinate and stakeholder businesses so that they can equate the views related to the development of local food and stakeholders can engage with the optimal local food  development becomes more leverage.